2016
DOI: 10.5604/01.3001.0012.6484
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Behaviours, Physical Activity and Perceived Life Satisfaction in the Academic Youth of Pedagogical Subjects in Cracow

Abstract: The aim of the study was to analyse the correlation between the level of satisfaction with life, health-related behaviours and physical activity in the group of academic youth studying pedagogical subjects at chosen universities in Cracow. The following variables were used and characterized: levels of satisfaction with life, health-related behaviours and physical activity. The study verifi es the hypothesis that the academic youth characterized by higher levels of satisfaction with life will be show a wider sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In studies, the conceptual and empirical significance of individual differences as an important prognostic factor in assessing prohealth behaviors has been demonstrated. In earlier studies among Polish students of PE and other teaching specializations, statistically significant tendencies toward an increase on the scale of pro-health behaviors and the level of physical activity along with the increase in life satisfaction (Kosiba et al, 2016) and with the intensification of some of the features of readiness for change (confidence, passion, and optimism), have been confirmed (Kosiba et al, 2019c). It has also been established that students who rate vital values higher (including fitness and physical strength as well as endurance) undertake physical activity more often (Kosiba et al, 2019a).…”
Section: Introductionmentioning
confidence: 85%
“…In studies, the conceptual and empirical significance of individual differences as an important prognostic factor in assessing prohealth behaviors has been demonstrated. In earlier studies among Polish students of PE and other teaching specializations, statistically significant tendencies toward an increase on the scale of pro-health behaviors and the level of physical activity along with the increase in life satisfaction (Kosiba et al, 2016) and with the intensification of some of the features of readiness for change (confidence, passion, and optimism), have been confirmed (Kosiba et al, 2019c). It has also been established that students who rate vital values higher (including fitness and physical strength as well as endurance) undertake physical activity more often (Kosiba et al, 2019a).…”
Section: Introductionmentioning
confidence: 85%
“…in turn, Posadzki et al [37] revealed significant positive effects of positively correlated psychological traits, including sense of self-efficacy, optimism, and sense of coherence, on the health-promoting behaviour of Polish students. A larger scale of health-promoting behaviours, including positive nutrition practices, along with an increase in the level of life satisfaction was also described in a group of Polish teaching specialization students [38]. relationships of life satisfaction with some health conditions including nutritional ones were also confirmed by iranian studies, showing a positive correlation between the level of life satisfaction and the number of meals, regular consumption of breakfast, as well as the frequency of fruit and vegetables consumption among medical students [39].…”
Section: Discussionmentioning
confidence: 93%
“…The existence of relationships between psychological features that are important in a teacher's daily work and in the prevention of professional burnout, such as self-efficacy, optimism, general life satisfaction and pro-health behaviours, indicate the results of research carried out in different population groups. In the research by G. Kosiba et al (2016a), the relationship between the level of life satisfaction and the intensity of pro-health behaviours in the area of positive mental attitude, every day pro-health practices, proper eating habits and preventive behaviours in students of teaching faculties was demonstrated. Lipowski's research (2012) showed a relationship between the level of optimism and some pro-health behaviours of women practicing sports.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, more and more connections between proper functioning at work and an individual's lifestyle are highlighted, and the importance of pro-health behaviours for broadly understood quality of life, including occupational life and satisfaction, is emphasised (Bailey, Hillman, Arent, Petitpas, 2013;Pedišić, Rakovac, Titze, Jurakić, Oja, 2014;Eime, Harvey, Payne, 2014;Maher, Pincus, Ram, Conroy, 2015;Kosiba, Gacek, Wojtowicz, Bogacz-Walancik, 2016a).…”
Section: Introductionmentioning
confidence: 99%